Structural Behavior of Reinforced Concrete Beams Incorporating Foamed Glass as Aggregates - Atrushi, Dawood S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Natural resources that are utilized in civil engineering applications can be saved by replacing them with some recycled materials to produce sustainable concrete with required mechanical and durability properties. In recent years, recycled glass is being used as aggregates in concrete production in many countries across the world. In the present study, the structural properties of reinforced concrete beams containing foamed glass (FG) as a partial natural coarse aggregate replacement are investigated. Five concrete mixes were employed to conduct the present study. The coarse aggregate was replaced with 0%, 25%, 50%, 75%, and 100% (by volume) of FG. Four point-loading flexural tests on beams were conducted up to failure. The results showed that the compressive strength was decreasing linearly with the increasing amount of FG. It was also observed that the ductility of the reinforced concrete beams significantly improved. However, the load-carrying capacity of the beam and load at which the first crack occurs was reduced. It was concluded that the inclusion of FG in structural concrete applications is possible and the structural behavior of concrete beams proved to be similar to that of other types of lightweight aggregate concrete such as wood and plastic aggregates used in similar structural elements.